English Pronunciation: Utilizing the English Pronunciation IPA Application to Help Students Pronounce the Words Properly - Andi Idayani; Satriani, Estika; Akhra, Inayah Dzahabiyah (Perspektif Pendidikan dan Keguruan, 2025)
Pronunciation is a fundamental aspect of English-speaking skills. This study aims to identify students' pronunciation errors when articulating English short vowels in the fifth semester of the English Language Education program using the English Pronunciation IPA application and to explore the factors contributing to these errors. A qualitative research design was employed, with data collected through pronunciation tests and interviews. The English Pronunciation IPA application was used as a tool to assist students in taking short vowel pronunciation tests. Five students were selected as interview participants. The study findings revealed that students achieved an average score of 15.57, with short vowels scoring 3.70 points. The most frequent pronunciation errors occurred with the /ɒ/ and /æ/ vowel sounds, where students exhibited significant difficulties and confusion. Most interviewed students admitted that they pronounced words based on their written form. The study concluded that language interference and phonological knowledge were key factors affecting students' pronunciation issues. This research is expected to provide valuable insights for teachers regarding students' pronunciation difficulties and serve as a reference for future studies in this area.